Young People's Voice in School Science Research from Five Years in the Classroom - Logan, Marianne (Cham : Springer Nature Switzerland : Imprint: Palgrave Macmillan, 2023)
This book highlights young people's changing attitudes toward and interest in science over the course of a five-year longitudinal study. Utilizing a mixed-methods approach, the author presents rich data from children and young people, as well as their parents and teachers. By providing a glimpse of science pedagogy from the perspective of young people and those who work with them, the book identifies factors that affect students' interest in science throughout their primary and secondary education. The book also examines a posthumanist philosophical approach to science education and emphasizes the interrelationship of all things within the context of science education. .
Chapter 1. The Grand Tour -- Chapter 2. Interest, Attitudes, Motivation and Engagement -- Chapter 3. The Philosophical Approach -- Chapter 4. Behind the research -- Chapter 5. Retaining High Interest in Science over Junior Secondary School -- Chapter 6. Losing Interest in Science over Junior Secondary School -- Chapter 7. Exploring the Schools, Classes, and Teachers, in the Case Study -- Chapter 8. Revelations.
Keywords: Science -- Study and teaching; Education; Children; Teaching; Environmental education; Science Education; Childhood Education; Pedagogy; Environmental and Sustainability Education